الأدوار المستقبلية لمعلم التربية الفنية في ضوء مهارات القرن الحادي والعشرون - فوزي، ياسر محمود (جامعة المنصورة - كلية التربية, 2020)
يهدف البحث الحالي تحديد أدوار معلم التربية الفنية في ضوء التوجهات المعاصرة لمعلم المستقبل والتي فرضتها مهارات القرن الحادي والعشرون، وقد تمحورت مشكلة الدراسة في الإجابة على الأسئلة التالية: ما العلاقة بين مقومات معلم التربية الفنية وبين تحقيق مؤشرات مرتبطة بمهارات القرن الحادي والعشرون؟، ما مدى تضمين الأدوار المتعددة لمعلم التربية الفنية لمؤشرات ترتبط بادؤه كمعلم فعال ومؤشرات الاستجابة المتوقعة من الطلبة؟ وقد اتبع الباحث إجراءات المنهج الوصفي خلال تصميم نموذج يتضح خلاله تحديد العمليات والمؤشرات المتوقعة للأدوار الجديدة لمعلم المستقبل، بالتزامن واستشراف مؤشرات الاستجابة المتوقعة من الطلبة. وقد تم تصنيف أدوار المعلم إلى معايير ومؤشرات على هيئة نموذج للاستبيان على صلاحيته تم توزيعه على لجنة من الخبراء في الميدان. أظهرت نتائج البحث ارتفاع نسب الاتفاق على المعايير والمؤشرات الخاصة بمواصفات معلم التربية الفنية المستقبلي. قدم البحث عددًا من التوصيات أهمها العمل على الأخذ بالمعايير المقترحة عند تطوير نظم اعتماد برامج التربية الفنية في المؤسسات الجامعية.
The current research aims to define the roles of the art education teacher in light of the contemporary trends of the future teacher imposed by the skills of the twenty first century. The study problem centered in answering the following questions: What is the relationship between the components of the art education teacher and the achievement of indicators related to the skills of the twenty first century? To what extent do the various roles of the art education teacher include indicators related to his performance as an effective teacher and the response indicators expected from students? The researcher followed the descriptive approach procedures during designing a model in which it is clear to define the expected processes and indicators for the new roles of the future teacher, in conjunction with exploring the expected response indicators from the students. The teacher's roles were classified into criteria and indicators in the form of a questionnaire on its validity, which was distributed to a committee of experts in the field. The results of the research showed high rates of agreement on the criteria and indicators for the specifications of the future art education teacher. The research presented a number of recommendations, the most important of which is to work on adopting the proposed standards when developing systems for accrediting art education programs in university institutions.
Keywords: المعلمين -- معلم المستقبل -- معلم التربية الفنية -- المهارات التدريسية -- مهارات القرن الحادي والعشرون